Analisis Filogenetik Lebah Madu Endemik Sulawesi Apis nigrocincta Smith, 1860 Berdasarkan Gen 16S rRNA - Hidyanisa, Dhea; Budiarsa, I Made; Ashari, Abdul; Trianto, Manap; Nurdin, Musdalifah; Windarsih, Yulia (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
Apis nigrocincta is an endemic honey bee that is only found in two regions in Indonesia, namely the Sangihe Islands and Sulawesi Islands. Phylogenetic analysis is used to describe the phylogenetic relationship of Sulawesi endemic honey bee A. nigrocincta based on the 16S rRNA gene. Sampling using the cruising method in various regions, then DNA isolation, DNA amplification, sequencing, and continued bioinformatics analysis using GeneStudio, DNASTAR, MESQUITE, and MEGA 11. The results showed that phylogenetic analysis with the Neighbor-Joining (NJ) and Maximum Likelihood (ML) methods produced a phylogenetic tree that illustrates clear evolutionary relationships. A. nigrocincta from Central Sulawesi is more closely related to other A. nigrocincta species in the same clade, while other species are separated. The results of this study show a clear pattern of kinship between A. nigrocincta populations.Â